The Authority of Al-Kutub Mu'tabarah in The Settlement of Sharia Economic Disputes in the Purbalingga Religious Court: A Study of Decision Number 1047/Pdt.G/2006/Pa.Pbg. - Azizah, Nurul; Tarmidzi, Tarmidzi; Hasanudin, Hasanudin; Sunaryo, Agus (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
Law No. 3 of 2006 concerning Amendments to Law No. 7 of 1989 concerning Religious Courts added the absolute competence of the Religious Courts in accepting resolving and deciding civil cases related to sharia economic disputes. The legal vacuum requires judges to refer to the yellow book or al-kutub al-mu'tabarah as a guide in resolving sharia economic cases in the Religious Courts. This article will look further at how the role and authority of the yellow book or al-kutub al-mu'tabarah in the settlement of sharia economic cases in the Purbalingga Religious Court. The Purbalingga Religious Court received sharia economic cases in 2006 six months after Law No. 3/2006 was published. this research is a qualitative research with a normative approach. Decision No. 1047/Pdt.G/2006/PA.Pbg. as the primary source. The results of this study indicate that the opinion of the fukaha in the yellow book or al-kutub al-mu'tabarah or popular books has an important position and even becomes the main reference in the settlement of sharia economic cases in the Purbalingga Religious Court. The book 'Iānah al-Ṭālibīn by Zainuddīn al-Malibārī and al-Fiqh al-Islāmī wa Adillatuh by Wahbah al-Zuḥailī play an important role in the settlement of sharia economic cases in the Purbalingga Religious Court.